THE PRACTICE OF EFFECTIVE USE OF SECURITIES IN THE FORMATION OF FINANCIAL RESOURCES OF COMMERCIAL BANKS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The practice of effective use of securities in the formation of financial resources of commercial banks plays a crucial role in enhancing their financial stability, profitability, and overall market competitiveness. This paper explores the strategic management of securities portfolios by commercial banks, focusing on key practices, benefits, and risks associated with different types of securities. The analysis delves into the methods of asset allocation, diversification, and risk management that banks employ to optimize their financial resources through securities. Furthermore, it examines regulatory frameworks and compliance requirements that influence banks' investment strategies. By integrating both theoretical perspectives and empirical data, this study provides insights into the evolving trends in securities utilization and their impact on banks' financial health. The findings underscore the importance of sophisticated financial instruments and advanced risk assessment models in achieving a balanced and profitable securities portfolio. Recommendations are proposed for enhancing the strategic use of securities to support sustainable financial growth and resilience in the banking sector.